2021
DOI: 10.1021/acs.orglett.1c02592
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Carbinol Cation/Anion Umpolung: Direct Addition of Aromatic Aldehydes and Ketones to Carbon Dioxide

Abstract: We have developed a new photocatalytic umpolung reaction of carbonyl compounds to generate anionic carbinol synthons. Aromatic aldehydes or ketones reacted with carbon dioxide in the presence of an iridium photocatalyst and 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzimidazole (DMBI) as a reductant under visible-light irradiation to furnish the corresponding α-hydroxycarboxylic acids through nucleophilic addition of the resulting carbinol anions to electrophilic carbon dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…4a). 23 To rule out a radical-radical coupling pathway, we confirmed the inertness of the electron-rich aldehydes and ketones undecanal (2H), 4fluoroacetophenone (2M), and acetophenone (2N) under the standard conditions (Fig. 4b and SI, Table S9).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…4a). 23 To rule out a radical-radical coupling pathway, we confirmed the inertness of the electron-rich aldehydes and ketones undecanal (2H), 4fluoroacetophenone (2M), and acetophenone (2N) under the standard conditions (Fig. 4b and SI, Table S9).…”
Section: Resultsmentioning
confidence: 79%
“…Surprisingly, when the reaction was carried out under a CO2 atmosphere, the cross-pinacol selectivity markedly improved, and 3aA was obtained in 77% NMR yield, along with a 7% yield of the homo-coupled dimer 4aa and a 9% yield of the ahydroxycarboxylic acid 6a (entry 2). 23 The presence of a small amount of CO2 (1 mL) was enough to promote cross-pinacol coupling, without the formation of the carboxylic acid 6a as a byproduct, giving 3aA in 67% yield together with a 13% yield of the homo-coupled product 4aa (entry 3). By a thorough screening of the reaction conditions, the NMR yield of 3aA was eventually increased to 82% along with 5% of diol 4aa when CO2 (5 mL) was bubbled through the solution for 30 seconds before irradiation under a N2 atmosphere; none of the a-hydroxycarboxylic acid 6a (entry 4) was formed [also see Table S5 in the Supplementary Information (SI) for details].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, Uozumi and Okumura disclosed a novel pathway when utilizing a photocatalytic umpolung strategy for the carboxylation of aromatic aldehydes and ketones in the presence of a photocatalyst and a reductant (DMBI) (Scheme 14). 25 Mechanistically, Stern–Volmer quenching experiments revealed that DMBI quenched the photocatalyst in an excited state. Ketyl radical 32 possibly coupled with CO 2 and was then-reduced by the strong reductant DMBI radical species 37 to give the key intermediate carbinol anionic species 34 .…”
Section: Carboxylation Of Co Bondsmentioning
confidence: 99%
“…This second possibility includes reductive activation of C-LG bonds (LG – is a leaving group, often a halide ion) ( Meng et al, 2017 ; Isse et al, 1998 ; Isse et al, 2002 ; Isse and Gennaro, 2002 ; Scialdone et al, 2008 ; Durante et al, 2013 ) of C=C or C=N double bonds ( Seo et al, 2017 ; Fan et al, 2018 ; Chen et al, 2020 ; Fan et al, 2018 ; Schmalzbauer et al, 2020 ) and of C-H bonds ( Gui et al, 2017 ; Seo et al, 2017 ; He et al, 2020 ). Recent examples include activation of substituted olefins ( Alkayal et al, 2020 ), of diverse carbonyl compounds ( Okumura and Uozumi, 2021 ) including α-ketoamides and α-ketoesters ( Cao et al, 2021 ), α,β-unsaturated esters ( Sheta et al, 2021 ) and ketones ( Chen et al, 2020 ), and of aldimines generated in situ for α-aminoacid synthesis ( Naito et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%